PERAN DAYA TARIK KONTEN, KEMUDAHAN PENGGUNAAN DAN KUALITAS INTERAKSI LAYANAN DALAM MENINGKATKAN PEMBELIAN DARING DI E-COMMERCE BLIBLI.COM DI PURWAKARTA - indra maulana; Rr Putri Suryaningwulan (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2020)
This study aims to obtain an overview of the implementation of content attractiveness, ease of use, quality of service interactions, online purchasing decisions, also to determine the effect of these variables both partially and jointly. Data collection uses purposive sampling technique by distributing questionnaires to 100 respondents who are e-commerce users of blibli.com in Purwakarta. The research data were then analyzed using SPSS 24. In general the implementation of content appeal, ease of use, quality of service interaction, online purchasing decisions at e-commerce blibli.com in Purwakarta has been going well. The results showed that partially, the three independent variables namely Content Attractiveness, Ease of Use and Service Interaction Quality had a positive and significant effect on Online Purchasing Decisions, where Service Interaction Quality had the most influence. And the entire Independent variable influences together (simultaneously) on Online Purchasing Decisions.